Behavioral management techniques in pediatric dentistry: A literature review - Uchôa, Sue Ann Castro Lavareda; Corrêa, Suelen Castro Lavareda; Corrêa, Davi Lavareda; Corrêa, Vânia Castro; Dias, Hércules Bezerra (Seven Editora, 2024)
Fear and apprehension related to dental care are considered a significant health challenge, often impeding the search for dental care. This obstacle takes on even greater proportions when it comes to children, as the effectiveness of procedures can be compromised if the dentist is not able to apply behavior management techniques. This study aims to address effective behavior management techniques to reduce fear and anxiety in child patients and their caregivers. To achieve this purpose, a literature review was carried out using the Virtual Health Library/LILACS, Pubmed and Scielo databases. The descriptors used included or combined: pediatric dentistry, fear, anxiety, child behavior. Children often experience fear and anxiety regarding dental treatment. To mitigate these feelings, it is crucial that the dentist knows and applies behavior management techniques, adapting them individually to each child and establishing a relationship of trust with both the child patient and their parents or guardians. This approach aims to minimize fear and anxiety, reducing the chances of behavioral problems, resulting in safe and smooth care. DOI: https://doi.org/10.56238/sevened2023.007-039